Dampak Penggunaan Artificial Intelligence (AI) Terhadap Peran Pendidik Sekolah Dasar di Era Merdeka Belajar - Sulton Akbar; Ikhtiatus Sholihah; Agung Setyawan (Suria Academic Press, 2026)
Artificial intelligence (AI) is increasingly prevalent in primary education, but previous research has tended to focus exclusively on its technological advantages without methodically examining how AI is transforming the role of educators at the pedagogical, ethical, and social levels. To address this gap, this article summarizes 10 published studies from the previous five years. According to the analysis, AI is taking over a number of operational tasks, including learning performance analysis, automated assessment, and personalization. This could ultimately lead to a shift in the role of educators to professional decision-makers who ensure the ethical alignment and pedagogical accuracy of system outputs. The results also indicate that educators' capacity to understand context, maintain learners' emotional components, and address algorithmic bias remains crucial to the quality of learning. Issues such as infrastructure disparities and the digital skills gap highlight the importance of institutional readiness for successful AI integration. A key contribution of this study is an analytical framework that systematically analyzes how educators' roles in AI-based learning ecosystems are evolving.